High speed machining of magnesium and its alloys - Danish, M. (Elsevier, 2020)
Magnesium (Mg) alloys, the lightest of structural materials on the earth, possess great potential to be used in important sectors such as automobiles, aerospace, and biomedical applications. Magnesium, which normally possesses good machinability, still can be difficult-to-cut due to its low melting point and ignition susceptibility. As such, the high speed machining (HSM) has tendency to cause built-up-edge-consequently poor surface finish and dimensional tolerance-and may cause ignition during machining. Evidently, advanced strategies, that is, proper tool design, controlled cutting parameters, cooling lubrication technologies, etc. are required for efficient HSM. Based on this perspective, this chapter focuses on the HSM of Mg alloys. After a general description of Mg alloys and its machining, this chapter sequentially discusses the state-of-art of Mg machining processes, different performance indicators, potential cooling-lubrication technologies, and finally the considerations for HSM of Mg. Here, special attention is given on the turning, milling, and drilling processes, wherein the cutting temperature, force, surface quality, residual stress, tool wear, energy, and microstructure are covered as key performance indicators. Â© 2020 Elsevier Inc. All rights reserved.